Learning Model based on Multiple Intelligences oriented towards Higher Order Thinking Skills (HOTS) through the application of Visual, Auditory, Read-Write Preferential, Kinesthetic (VARK), and Directed Reading Listening Thinking Activity (DRLTA) in Elementary School - Suhartono Suhartono; Hanafi Hanafi; Cici Murniasih; Moch. Noviadi Nugroho (Research and Innovation in Social Science Education Journal (RISSEJ), 2025)
The purpose of this study was to develop a learning model based on multiple intelligences and students' critical thinking skills through visual, auditory, preferential read-write, kinesthetic (VARK) learning strategies, and the application of the directed reading listening thinking activity (DRLTA) model to elementary school students. The stages include: 1) formulating research problems and determining survey objectives, 2) determining concepts and hypotheses and digging literature, 3) sampling, 4) making kueisoner, 5) field work, 6) data processing, 7) analysis and reporting. The result of the need assessment score is 3.54, the product development stage, FGD, expert and practitioner validation and the field trial stage. The feasibility of this model is tested based on: 1) The assessment of psychologists is assessed based on three aspects, namely the elements of the supporting theory used, the elements of the learning stages and the elements of the implementation of learning techniques to get a score of 4.77 or including "very feasible" to use. 2) Assessment of education practitioners is also assessed based on three aspects of getting a score of 4.33 or including "very feasible" to use. 3) Field trial assessment based on four aspects, namely, Multiple Intelligences detection, learning methods and learning media. Field trials were carried out with the individual trial stage getting a score of 3.56 including "very feasible", group field trials resulting in a score of 3.59 including "very feasible" and limited field trials getting a score of 3.8 including "very feasible" to use. The framework in this study is based on quantitative and qualitative research in accordance with the objectives to be achieved, the research problems to be solved, and the nature of the data required. The use of a mixed method approach is based on research coverage and research problems. In accordance with the objectives and research problems and the nature of the data collected, this study used a two phase design. The reason for using this design is that it allows theoretically and practically the development of two designs in a position to complement each other, equal, and be implemented sequentially.